Opportunities to Target T Cell Trafficking in Pediatric Inflammatory Bowel Disease - Giannoudaki, Eirini; Gargan, Siobhan; Hussey, Seamus; Long, Aideen; Walsh, Patrick T. (Frontiers in Pediatrics, 2021)
T cell subsets are considered central orchestrators of inflammation and homeostasis in the intestine and are established targets for the treatment of inflammatory bowel disease. While approaches aimed at the neutralization of T cell effector cytokines have provided significant benefits for pediatric and adult patients, more recent strategies aimed at inhibiting the infiltration of pathogenic T cell subsets have also emerged. In this review, we describe current knowledge surrounding the function of T cell subsets in pediatric inflammatory bowel disease and outline approaches aimed at targeting T cell trafficking to the intestine which may represent a new treatment option for pediatric inflammatory bowel disease.